The Legal Framework Issue of International Commercial Arbitration in Iraq - Badr Mohammed Taher Mustafa; Miran Mamand Bayz Agha (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The globalization phenomenon altered all aspects of human life, including commerce, when Confronted with a more intricate problem, in this case, arbitration becomes a sound option to adjudicate between the parties to an international commercial contract. In this research, researcher intend to disclose the significance of international commercial arbitration legal framework and its method of solving commercial disputes in Iraq as an alternative to court litigation.